Ventajas de la medición de niveles plasmáticos de infliximab en pacientes con enfermedad inflamatoria intestinal - Rojas B., René; Covarrubias R., Natalia; Miranda B., Julio; Pérez de Arce O., Edith; Gompertz G., Macarena (Revista Hospital Clínico Universidad de Chile, 2016)
Inflammatory bowel disease includes Crohn ́s disease, ulcerative colitis and unclassified colitis. Conventional therapies used for treating these diseases are often insufficient or contraindicated and biological agents have proved to be effective and safe in these cases. Infliximab is a quimeric IgG1 monoclonal anti-tumor necrosis factor antibody that is capable of inducing and mantaining clinical remission in patients with inflammatory bowel disease. Despite its proven efficacy a considerable group of patients lose response requiring changes in therapy. Serum Infliximab trough levels are correlated with clinical response, endoscopic remission and mucosal healing in patients with inflammatory bowel disease. Monitoring and adjusting therapy guided by drug serum levels have proved to be more cost-effective and safer than empiric adjustments. Current international guidelines recommend the measurement of Infliximab trough levels in the global evaluation and management of these patients to improve treatment, avoid adverse events and unnecessary costs.